2020
DOI: 10.1093/nutrit/nuaa097
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet and offspring telomere length: a systematic review

Abstract: Context Many studies assert a negative influence of inappropriate maternal diet and nutritional status during pregnancy on offspring, not only in utero but throughout life, because of the role in the programing of noncommunicable diseases. Telomere length is a biomarker of aging, and shorter telomeres are associated with chronic disease later in life. Maternal nutrition and nutritional status may be an important determinant of offspring telomere length. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Multiple findings indicate that TL may be also significantly modulated by environmental and life-style factors throughout the life course. Among important factors affecting life-course TL dynamics, there are developmental experiences such as intrauterine unfavorable events (Entringer et al, 2018 ; Habibi et al, 2020 ), TL at birth (Gorenjak et al, 2020 ), as well as early life adversity (family's low socioeconomic status, childhood neglect or abuse, etc.) (Belsky and Shalev, 2016 ; Ridout et al, 2018 ; Beijers et al, 2020 ).…”
Section: Genetic and Environmental Determinants Of Tlmentioning
confidence: 99%
“…Multiple findings indicate that TL may be also significantly modulated by environmental and life-style factors throughout the life course. Among important factors affecting life-course TL dynamics, there are developmental experiences such as intrauterine unfavorable events (Entringer et al, 2018 ; Habibi et al, 2020 ), TL at birth (Gorenjak et al, 2020 ), as well as early life adversity (family's low socioeconomic status, childhood neglect or abuse, etc.) (Belsky and Shalev, 2016 ; Ridout et al, 2018 ; Beijers et al, 2020 ).…”
Section: Genetic and Environmental Determinants Of Tlmentioning
confidence: 99%
“…A metanalysis of seven double-blinded studies showed that higher concentrations of maternal folate and 25-hydroxyvitamin D3 as well as dietary caffeine consumption were associated with longer telomere length in newborns. In contrast, higher consumption of carbohydrates, fatty acids, vitamin C or sodium, did not associate with longer telomeres in the offspring [100]. Alcohol consumption disorders shorten adult LTL [101].…”
Section: External Factors and Telomeres In Newbornsmentioning
confidence: 66%
“…Telomeres may also be susceptible to poor or unbalanced nutrition. It has been reported that TL in the offspring is positively related to folate, vitamin D, and caffeine concentrations in maternal diet (24), but negatively related to maternal saturated fat intake during pregnancy and prepregnancy BMI (25,26). In addition, n-3 polyunsaturated fatty acids (n-3 PUFAs) may be a factor that prevents telomere shortening in cell division, for which they have anti-inflammatory and anti-oxidative effects, particularly, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%